Genetic Risk Analysis of Gestational Diabetes Mellitus in a Turkish Population - Dudu Erkoç-Kaya; Hilal Arikoglu; Funda Iscioglu; Suleyman Hilmi Ipekci (Research in Molecular Medicine, 2021)
Background: Gestational diabetes mellitus (GDM) is a type of clinical diabetes characterized by insulin resistance and impaired insulin secretion because of environmental and genetic factors. The high risk of developing type 2 diabetes (T2D) in women with GDM and the high risk of developing GDM in women with a family history of T2D suggests that both diseases may have the same genetic basis. Therefore, genes and risk variants associated with the genetic architecture of T2D are being investigated for their effects on the development of GDM. In this study, we aim to investigate ABCC8, TCF7L2, Adiponectin, IRS1, and PPARG genes, which are known as T2D risk genes, to understand the genetic basis of GDM in a Turkish population.